POLA PERTUMBUHAN, FAKTOR KONDISI DAN HABITAT IKAN TEWARING Barbodes binotatus (Valenciennes, 1842) DI SUNGAI HUTAN BERAMBAI SAMARINDA - Pratama, Rynaldo; Jusmaldi, Jusmaldi; Hariani, Nova (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The research about growing pattern, condition factor and habitat of Spotted Barb Barbodes binotatus (Valenciennes, 1842) was done from August until December 2017. The aims of this research are to know growing pattern, condition factor, sex ratio and habitat of Spotted Barb (Barbodes binotatus) in Berambai Forest River. Fishing was done in every month, using purposive sampling method with some fishing gears. The result of the research shows that growing pattern of Spotted Barb (B. binotatus) was positive allometric, the average value of the condition factor was 1,064. The sex ratio of male and female were 1 : 1,06. The Berambai River in good condition for living of Spotted barb.